A Guide to stock-trading decision Making based on popular Technical Indicators - Kouatli, Issam (2021)
The purpose of this paper is to review the different mechanisms of decision-making when making a trade in the stock market industry. Decisions of “sell” and “buy” are highly dependent on the type of data collected which are mainly divided into two main types: “trend following” and “mean revert”. Different Technical Analysis (TA) indicators are used by professionals in the stock trade industry as an aid towards taking a decision. This paper reviews these technical indicators and suggest a strategy to identify and adopt the right technical indicator based on the data behavior.